Leveraging new methodologies for public health crisis management - Khalil, Hanan; Marcucci, Joanne; Liu, Chaojie (Frontiers in Public Health, 2024)
Evidence-based medicine is critical in public health emergencies, offering a framework for decision-making and adaptive healthcare responses. By relying on up-to-date and reliable evidence, EBM enables healthcare systems to respond quickly to evolving crises and ensures efficient resource allocation. This perspective presents the importance of evidence-based medicine in public health emergencies, emphasizing the need for rapid decision-making and preparedness. It identifies challenges from the COVID-19 pandemic, including barriers to evidence synthesis, and explores innovative solutions, including methodological pluralism and systems thinking. The findings highlight that evidence-based medicine improves health care systems’ responsiveness to public health crises, supports the efficient resource allocation, and reinforces the need for flexible strategies that adapt to rapidly evolving information. In particular, the practical implications underscore that, in crisis settings, EBM must expand beyond strict evidence hierarchies to include timely, reasonable, and sometimes intuitive expert judgments, ensuring robust and adaptable responses. In conclusion, while EBM enhances healthcare adaptability and decision-making in emergencies, future responses will benefit from incorporating more diverse and flexible approaches to ensure more resilient and effective public health strategies.